PREVALÊNCIA DE HEPATITE B E C NA POPULAÇÃO DE CAMINHONEIROS DA ROTA DE INTEGRAÇÃO LATINO AMERICANA EM CAMPO GRANDE/MS - SILVA, Geovanna; GARDENAL, Renata; MACHADO, Alessandra; BENETTI, Bruna; SOUZA, Cristal; LEMOS, Everton (ANAIS DO ENIC, 2025)
.